Integration of phospho-signaling and transcriptomics in single cells reveals distinct Th17 cell fates - Seth D. Fortmann; Awalpreet S. Chadha; Blake F. Frey; Asif Elahi; Vidya Sagar Hanumanthu; Shanrun Liu; Andrew Goldsborough; P. Brent Ferrell, Jr.; Maria B. Grant; Casey T. Weaver; Robert S. Welner (Cell Reports, 2025)
Summary: Single-cell RNA sequencing (scRNA-seq) provides the resolution and scale necessary to identify transcriptional programs but fails to capture post-transcriptional information critical to decipher signaling networks and cellular states. We present Vivo-seq, an innovative platform that integrates scRNA-seq and intracellular cellular indexing of transcriptomes and epitopes by sequencing following cellular fixation with a deep eutectic solvent, which preserves multiple domains of biological information beyond RNA transcripts alone. Vivo-seq enables simultaneous capture of both transcriptional and phospho-signaling states in single cells. Applying this platform to developing T helper 17 (Th17) cells, we find that simultaneous phosphorylation of ERK1/2 and c-FOS leads to maximal interleukin-2 (IL-2) and IL-17 production. Furthermore, we show that early IL-2 production imprints developing Th17 cells for enhanced maintenance or cytokine-dependent transdifferentiation during subsequent antigenic stimulation. By integrating transcriptional and phospho-signaling information at single-cell resolution, we identify a hyperactivated Th17 cellular state associated with early IL-2 production that has downstream consequences on functional plasticity.